Labor costs and productivity trends in selected Brazilian manufacturing industries: An international comparison - Hartmut Picht (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1987)
The analysis focuses on the iron and steel industry, the motor vehicle and the non-electrical machinery industry as well as the manufacture of wearing apparel and footwear. The iron and steel industry and the motor vehicle industry were chosen, because they are characterized by low to middle skill level, capital-intensive production processes (Wolter 1974, 66-67; Walter 1982, 1; Humphrey 1982, 101; Kageyama, 1984, 25). The non-electrical machinery industry was selected, because it depends traditionally more on skilled labor, and less on physical capital (Dick 1981, 30; UNIDO 1984, 5 and 60). Finally the wearing apparel and the footwear industries represent the case of labor-intensive production processes that draw mainly on unskilled labor (Pearson 1983, 65; ILO 1979, 30). Throughout the analysis all manufacturing is used as a common benchmark. Reference is made to major competing newly industrialized countries, i.e., South Korea, Taiwan, Hong Kong, and Mexico, as well as to industrialized countries such as the United States, Spain, Japan, and the Federal Republic of Germany. Section II will clarify the most important conceptual and methodological issues and some shortcomings of previous labor cost analyses, and lay the ground for the empirical investigation pursued in this study. Partial findings of previous studies on Brazilian labor costs will be referred to as complementary information in the empirical part of the study (Section III). In Section IV the major results of the analysis will be summarized.
Keywords: 330; Arbeitskosten; Arbeitsproduktivität; Brasilien